2021
DOI: 10.3892/ol.2021.13114
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FOXD3‑AS1 promotes the progression of non‑small cell lung cancer by regulating the miR‑135a‑5p/CDK6 axis

Abstract: Long non-coding RNA (lncRNA) is essential to the development and progression of malignant human cancer. Growing evidence suggests that the lncRNA forkhead box D3 antisense 1 (FOXD3-AS1) is a crucial regulatory effector for multiple cancer types and is closely associated with poor prognosis. However, in most cases, the molecular mechanism underlying the role of FOXD3-AS1 in cancer development has not yet been fully elucidated. The present study focused on non-small cell lung cancer (NSCLC) in order to gain insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Through the PI3K/Akt pathway, FOXD3-AS1 interacts with and activates RNA-binding protein ELAV-like RNA-binding protein 1, causing LC cell proliferation, invasion, and 5-fluorouracil resistance [ 20 ]. FOXD3-AS1 has also been shown to keep mediator subunit 28, murine double minute 2, and cyclin-dependent kinase 6 expressions in NSCLC by sequestering miRNAs [ 21 23 ]. We confirmed that FOXD3-AS1 is overexpressed in both blood and tissues of LUAD, LUSC, and SCLC samples when compared to control in the current study, based on hints from the Cancer Genome Atlas (TCGA) lung adenocarcinoma projects, lung squamous carcinoma projects, and Gene Expression Omnibus (GEO) datasets (GSE60052) as well as our RT-qPCR assays.…”
Section: Introductionmentioning
confidence: 99%
“…Through the PI3K/Akt pathway, FOXD3-AS1 interacts with and activates RNA-binding protein ELAV-like RNA-binding protein 1, causing LC cell proliferation, invasion, and 5-fluorouracil resistance [ 20 ]. FOXD3-AS1 has also been shown to keep mediator subunit 28, murine double minute 2, and cyclin-dependent kinase 6 expressions in NSCLC by sequestering miRNAs [ 21 23 ]. We confirmed that FOXD3-AS1 is overexpressed in both blood and tissues of LUAD, LUSC, and SCLC samples when compared to control in the current study, based on hints from the Cancer Genome Atlas (TCGA) lung adenocarcinoma projects, lung squamous carcinoma projects, and Gene Expression Omnibus (GEO) datasets (GSE60052) as well as our RT-qPCR assays.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that lncRNA FOXD3-AS1 is abnormally expressed in various human diseases, including lung cancer (24)(25)(26)(27)(28), breast cancer (29,30), cervical cancer (31,32), nasopharyngeal carcinoma (33,34), osteosarcoma (35), colorectal cancer (36), melanoma (37,38), liver cancer (39), thyroid cancer (40), neuroblastoma (41), glioma (42), allergic rhinitis (43), retinal infection with Toxoplasma gondii-ocular toxoplasmosis (44), ischemic stroke (45), myocardial ischemia (46,47) and acute respiratory distress syndrome (48). Further studies demonstrated that aberrant expression of FOXD3-AS1 is closely associated to clinicopathological characteristics, such as tumor size, tumor grade, distant lymph node metastasis, differentiation of tumor tissues, overall survival, progressionfree survival, and survival time of patients (Table 1).…”
Section: The Role Of Lncrna Foxd3-as1 In Diseasesmentioning
confidence: 99%
“…Despite advancements in early detection and treatment of NSCLC, the identification of molecular markers associated with patient survival is still necessary (53,(58)(59)(60). Multiple studies have demonstrated that FOXD3-AS1 is overexpressed in NSCLC tissues and cell lines (H1299, A549 and SPC-A1 cells) (24,(26)(27)(28). In addition, FOXD3-AS1 exerts pro-cancer effects in vitro and in vivo by regulating cell proliferation, migration, apoptosis as well as chemo-resistance.…”
Section: Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations